DEFINITION OF PRIORITY AREAS FOR FITNESS USE OF LAND THROUGH THE ANALYSIS MULTICRITERIA - Corseuil, Cláudia Webber; Campos, Sérgio; Pissarra, Teresa Cristina Tarlé (ENERGIA NA AGRICULTURA, 2015)
This paper aims to investigate the suitability of land use in a watershed by using the multicriteria decision analysis processing in a geographic information system (GIS) - 15.0 Idrisi Andes. The data selection and acquisition was based in a digital map product adopted in a 1:50000 scale; in a soil use watershed map, and in a Landsat 7 ETM + satellite image. The criteria set was based on some restriction to the farm management: permanent preservation areas, main roads, land use, slope and vegetation cover. This conflict was been resolved by applying the multi-criteria analysis using a weighting procedure such as the analytical hierarchy process (AHP) and the linear weighting combination (FTA), in a GIS processing. The results showed that the environmental shows agricultural and environmental characteristics, mainly due to the large extension of land available for agricultural use. KEYWORDS: Environmental planning, analytical hierarchy process, linear weighting combination. DEFINIÇÃO DE ÁREAS PRIORITÁRIAS PARA ADEQUAÇÃO DO USO DAS TERRAS POR MEIO DA ANÁLISE MULTICRITÉRIAL RESUMO: Esse trabalho objetivou a análise da adequação do uso de terras de uma microbacia pelo método de análise de multicritérios através do Sistema de Informação Geográfico (SIG) – Idrisi Andes 15.0, tendo como base cartográfica digital em escala 1:50000; o mapa do uso da terra da microbacia e imagens do satélite Landsat 7 ETM+. Os critérios usaram (restrições para a exploração agrícola): áreas de preservação permanentes, rede de estrada, uso da terra, declividade e cobertura vegetal. Para a análise de multicritérios, os métodos usados foram Processo de Hierarquia Analítico (AHP) e combinação linear ponderada (ACL), na plataforma de processamentoem SIG. Osresultados permitiram concluir que o ambiente apresenta características agrícolas e ambientais devido, principalmente, a ampla extensão de terra disponível para uso agrícola. PALAVRAS-CHAVE: Planejamento ambiental, Processo de Hierarquia Analítico, combinação linear ponderada.